ENGLISH AND TAGALOG VOCABULARY OF PRESCHOOLERS: A CONTRASTIVE ANALYSIS - Lumabi, Bethany Marie Cabantac; Maleon, Jeremie Monter (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2022)
In Philippine schools, the standard use of English and Tagalog is emphasized; code switching is discouraged. Therefore, parents of children who are exposed to and are trying to learn either of these languages, their L2 mind distinguishes correct usage of its features to avoid confusion and acquisition difficulties. Considerably, the English language acquisition in the Philippines is both influenced by nationwide use of the language in the households and communities, and exposure to information technology; both are deemed necessary in English literacy and prestige. Consequently, this case study contrasted the lexical and contextual features of L1 and L2 learned vocabulary words of pre-schoolers (male and female) to recognize their L2 acquisition difficulty and contextual cues as perceived by the parents of the subjects based on children’s personal, cognitive, and cultural attributes. Through qualitative method using the contrastive analysis hypothesis established by Lado (1957), this study supports the interlanguage of English and Tagalog; children can acquire lexical and contextual L1 and L2 prior to their formal schooling.